APPLYING SCIENTIFIC APPROACH TO ENHANCE INDONESIAN EFL LEARNERS’ DESCRIPTIVE WRITING PERFORMANCE - Fahrus Zaman Fadhly; Nurendah . (English Review: Journal of English Education, 2014)
Abstract: This study investigated the use of scientific approach to enhance students’ descriptive writing skill of seventh grade students in one of junior high schools in Kuningan, Indonesia. The use of scientific approach was examined based on Cuff and Payne (1979), Educational staff development center of ministry of education and culture (2013), and Syahmadi (2014) while students’ attitude was examined using a theory of Wenden (1991), and Gardner (1985). The writer used mix method study. Two instruments were used to get the data needed: test of descriptive text and questionnaire. The result showed that the Ha was accepted and the Ho was rejected as the t observed was higher than t table. Students’ descriptive writing skill in the experimental class enhanced since they were treated throughout scientific approach. It could be seen from the result of post-test (7.89) which increased significantly from pre-test result (3.697). This study also revealed that students’ attitude toward the approach was positive during the treatment. Moreover, this study proved that scientific approach enhanced students’ descriptive writing skill in one of junior high schools in Kuningan, Indonesia  and gave positive impact to the students.Keywords: scientific approach, descriptive text, attitude